Ethical Issues In Public Health Research - Mohammad Nurunnabi, Abu Sadat; Jahan, Mahmood Uz; Tanira, Shaorin (Bangladesh Journal of Bioethics, 2012)
Public health is the societal approach to protecting and promoting health. Public health ethics can be defined as the identification, analysis, and resolution of ethical problems arising in public health practice and research. The emerging interest in ethical issues in public health research and practice reflects both the important societal role of public health and the growing public interest in the scientific integrity of health information and the equitable distribution of health care resources. This article provides an overview of ethical issues in public health research for young researchers and readers who do not necessarily have an in-depth knowledge of public health ethics. A framework of ethics analysis geared specifically for public health is needed to provide practical guidance for public health professionals and researchers in Bangladesh. Bangladesh Medical Research Council is playing a role in setting a standard in the field of biomedical research including public health concerning its strategy and ethical issues and by helping different health institutes to build up a research environment. Though public policy is based on many factors in addition to public health goals and ethical reasoning, it should not lead to the politically preferable option for a given time. DOI: http://dx.doi.org/10.3329/bioethics.v1i3.9630 Bangladesh Journal of Bioethics 2010; 1(3): 15-21